(untitled) (American Journal of Education and Technology, 2023)
The study probed the integration of technology in Science instruction in relation to the students’ performance in National Achievement Test (NAT) results. It utilized a researcher-made questionnaire to obtain the data. The respondents of the study were the upper and lower 30% performing schools in the National Achievement Test (NAT) for the aforementioned school years. Results of the study revealed that the available technological resources for use in Science instruction in Butuan City Division for the upper 30% were printer, desktop computer, and Internet connection while for the lower 30% were desktop computer, printer, and speaker; that the level of technological skills of both the 30% school-respondents were rated expert in creating a presentation, using social networks, and their knowledge to operate computer. For the level of implementation in Technology-Assisted Science instruction the respondents were rated occasionally. On the other hand, data revealed that the relationship between the level of technological skills of the teachers, school’s implementation in Technology-Assisted Science instruction, and the performance in Science NAT between the upper and lower 30% school-respondents was significant. In conclusion, school-participants considered lack of computer sets as the major challenge they faced upon the implementation of Technology-Assisted Science instruction.